1999
DOI: 10.2337/diacare.22.4.598
|View full text |Cite
|
Sign up to set email alerts
|

Possible sources of discrepancies in the use of the Semmes-Weinstein monofilament. Impact on prevalence of insensate foot and workload requirements.

Abstract: Using a combination of sites 3 and 4 for monofilament testing gives a reasonable compromise for time, sensitivity, and specificity. Minor changes in sensitivity and specificity can lead to major changes in the prevalence of neuropathy, with implications for workload.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
54
1
7

Year Published

2000
2000
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 0 publications
1
54
1
7
Order By: Relevance
“…The use of monofilaments in practice has been supported by research that has demonstrated their capacity to identify patients at risk for ulceration (13,18,(21)(22)(23)(24)(25)(26)(27)(28). However, many researchers who have advocated the use of monofilaments have had the benefit of calibrating their monofilaments before use (22,23,28). Clinicians in practice are rarely able to access calibration equipment or procedures and have relied on the minimal data provided by manufacturers as an assurance of monofilament reliability.…”
Section: Accuracy Of Monofilamentsmentioning
confidence: 99%
See 4 more Smart Citations
“…The use of monofilaments in practice has been supported by research that has demonstrated their capacity to identify patients at risk for ulceration (13,18,(21)(22)(23)(24)(25)(26)(27)(28). However, many researchers who have advocated the use of monofilaments have had the benefit of calibrating their monofilaments before use (22,23,28). Clinicians in practice are rarely able to access calibration equipment or procedures and have relied on the minimal data provided by manufacturers as an assurance of monofilament reliability.…”
Section: Accuracy Of Monofilamentsmentioning
confidence: 99%
“…McGill et al (28) highlighted the effect of misdiagnosing sensate patients as insensate in their work on monofilaments. That research showed that a minor reduction in the specificity of monofilament testing resulted in 388 patients incorrectly recruited for specialist education and intervention.…”
Section: Accuracy Of Monofilamentsmentioning
confidence: 99%
See 3 more Smart Citations